Noninvasive monitoring of motor units in isometric and dynamic contractions - Merletti, R. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
While sport scientists deal with dynamic (often explosive) muscle contractions, researchers deal with isometric contractions, far easier to analyze. The strong time-varying contractions produced in sports change the length and pinnation of the muscle fibers and generate relative movement between the signal sources and the surface electrodes which affect the burst-like non-stationary interference EMG signals. The motor unit (MU) pool and the EMG amplitude and spectral variables change rapidly in time and no standards exist yet concerning the processing and interpretation of the signal. Intermittent contractions allow some recovery of membrane features and, together with the MU pool variability, blur the concept as well as the estimation of myoelectric manifestations of muscle fatigue. Published works in the field are hard to compare. Usually great caution is recommended in the interpretation of dynamic signals (Farina D., Interpretation of the surface EMG in dynamic conditions, Exerc. Sport Sci. Rev., 34, 121-127, 2006). The only confirmed application of surface EMG in dynamic conditions is the estimation of muscle activation intervals (see work of P. Bonato and A. Merlo). Masuda et al. in 1985 published a number of papers concerning surface linear electrode arrays for the identification of individual motor unit action potentials (MUAP). Since then, other researchers adopted and expanded in 2D this technique and were able to decompose the surface signals into the constituent MUAPs (see works of M. Gazzoni, A. Holobar, S. Karlsson, D. Stegeman). Tracking individual MUs may be more meaningful than monitoring the interference signal. At this moment the recruitment and derecruitment thresholds and the firing rate of the 5-10 MUs with the largest MUAPs may be observed during isometric forcevarying ramp-like contractions and in dynamic conditions with slowly changing joint angles. The joint angle must change slowly enough to allow the algorithm to track the MUAP shape changes resulting from the changing muscleelectrode geometry. In isometric or slowly changing dynamic conditions, tracking of a MUAP train allows monitoring the conduction velocity (CV) of the corresponding MU and its classification according to the CV initial value and rate of change versus time. Some evidence suggests that this may allow inference on MU type. Mapping of the surface potential during time provides information on the changing portions of muscle (compartments ?) during sustained or cyclic efforts. In conclusion, the use of surface EMG in dynamic conditions is in its infancy and is today limited to the identification of muscle activation intervals. Preliminary results obtained using 2D electrode arrays are very promising for the future but not yet reliable enough and movement and sport scientists must be patient for a little longer. In the meantime a badly needed effort for standardization of the analysis of EMG during isometric contractions should be undertaken.